COVID-19 pandemic decreased sleep quality of medical students - Ana Clara Aragão Fernandes; Deborah de Melo Magalhães Padilha; Anaís Concepción Marinho Andrade de Moura; Carlos Eduardo França de Aquino; Irinna Bruna de Araújo Lima; Sergio Arthuro Mota-Rolim (Sleep Science, 2022)
Objective: Medical students are especially vulnerable to situations of poor sleep quality due to academic demands. The COVID-19 pandemic brought significant changes and high psychological stress, causing a great impact on this population. Here we aim to analyze the influence of the pandemic on the sleep quality of medical students. Methods: Cross-sectional, observational, and descriptive study with a quantitative approach carried out with students from medical universities in Rio Grande do Norte state (Brazil) through the online application of two questionnaires: Pittsburgh sleep quality index (PSQI-BR) and sociodemographic questionnaire (SQ). Results: A total of 142 medical students participated in this study: 103 women and 39 men. We observed a prevalence of low sleep quality in 78.16% of the sample and that the pandemic significantly affected the sleep quality among medical students (p<0.05). We also found an alteration in the sleep pattern in 83% of the participants, mainly due to anxiety symptoms (38%). Finally, we observed no statistically significant difference in sleep quality or sleep patterns between genders or college period (p>0.05). Discussion: This rate of poor sleep quality is higher than the prevalence of periods before the pandemic (58%). Concerns about COVID-19’s negative impact on medical education, delayed training, and impact on the generation of medical jobs can directly aggravate the sleep quality. Conclusion: The COVID-19 pandemic negatively influenced the sleep quality of medical students, increasing the prevalence of poor sleep quality and promoting changes in the sleep pattern.